2000
DOI: 10.1046/j.1423-0410.2000.7820101.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Plateletpheresis Induces the Interaction of Activated Platelets with White Blood Cells

Abstract: This study demonstrates that platelets become activated during apheresis and that following this process, interaction with monocytes and neutrophilic granulocytes occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These interactions may activate platelets moreover contaminating small amount of endotoxin which occurs in PCs as storage time increase. [ 3 9 10 11 12 ] Can activate many types of cells in the concentrate to produce RANTES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions may activate platelets moreover contaminating small amount of endotoxin which occurs in PCs as storage time increase. [ 3 9 10 11 12 ] Can activate many types of cells in the concentrate to produce RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…Gutensohn et al . [ 11 ] demonstrated that in apheresis using Amicus, there is activation of platelets and there is interaction with monocytes and granulocytes. After the preparation of SDP with Amicus, lots of big aggregates was found, this finding was also observed by Hagberg et al .,[ 13 ] who showed that platelets from Amicus have increased fibrinogen receptor activation, increased the size of platelet aggregates, increased the formation of microparticles, increased degranulation, decreased von Willebrand factor receptor surface expression, and also decreased responses to in vitro agonist stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure causes leukocyte activation, inducing an increase in plasma tumor necrosis factor (TNF)-alpha levels; however, this has not been shown to impair endothelial cell function [55]. In addition, platelets become activated during apheresis and have been shown to interact with leukocytes [56]. Contact of platelets with artificial surfaces induces transient increases in platelet-derived soluble growth factors [57].…”
Section: Discussionmentioning
confidence: 99%
“…This function is attributed to professional phagocytes equipped with specific receptors for PS, such as the class B scavenger proteins SR‐ BI and CD36 (10–13). This phenomenon means that platelets with a high PS content in the outer plasma membrane could be removed after transfusion by the reticuloendothelial system independently of their functional status (10,11,14,15). These events may play an important role in the removal of senescent platelets from the circulation (12,13).…”
Section: Introductionmentioning
confidence: 99%